Kajian Tingkat Risiko Kerusakan Komponen Jalan Rel Menggunakan Metode Failure Mode and Effect Analysis (FMEA) : Studi Kasus Divre IV Tanjung Karang - Kristianto Usman; Agilia Rahma Winata; Nurwanda Sari; Febriyadi (UNIB Press, 2026)
This study applies the Failure Mode and Effect Analysis (FMEA) method, supported by expert opinion, to identify and prioritize damage risks in railway track superstructure components consisting of rails, sleepers, and fastening systems. The case study was conducted on the Divre IV Tanjung Karang railway section at KM 16+00-KM 20+00 using a descriptive quantitative approach. The analysis translates field observations and expert judgments into Severity, Occurrence, and Detection scores to calculate the Risk Priority Number (RPN). The results show that horizontal rail wear, rail-head defects, and cracks at welded joints are the most critical failure modes in rail components; broken sleepers are the main risk in sleeper components; and missing/vandalized fastenings and broken fastenings are critical risks in fastening components. Failure modes were categorized into high risk (RPN > 150), moderate risk (RPN 121-150), and low risk (RPN <= 120). The recommended mitigation emphasizes integrated preventive and corrective maintenance through routine inspection, condition monitoring, control of track geometry and loading, and timely repair or replacement of critical components to improve track infrastructure reliability and railway safety.